Looking back : Wide Awake Livery Stable (Raton, NM Raton Range, 1978)
Article is about the crew at Wide Awake Livery Stable posing for a 1910 photograph.
Newspaper article + Photograph of Wide Awake Livery Stable
Master list item #: 16
File location is in the Raton file Cabinet
Keywords: Floyd, Joe; Thompson, Lottie; Wide Awake Livery Stable; International State Bank; Buildings History; Business Buildings; Stables; Work Crews; Raton, New Mexico